2017
DOI: 10.1016/j.foodhyd.2017.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Insoluble soybean polysaccharides: Obtaining and evaluation of their O/W emulsifying properties

Abstract: a b s t r a c tThe aims of this work were to obtain different samples of insoluble soybean polysaccharides (ISPS) from defatted soy flour and to study their potential application as O/W emulsifier. In this regard, the insoluble residue (okara) resulting from an aqueous extraction (60 C, pH 9.0), was submitted to an acidic extraction (pH 3.5, 120 C) without or with a pretreatment (high pressure homogenization or sonication). The insoluble residues of these extractions were dried (oven, 70 C or vacuum post-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 37 publications
1
30
0
3
Order By: Relevance
“…No changes were observed in the %BS profiles or the %BS average values, so the emulsions were stable against creaming and coalescence. Porfiri et al ., working with insoluble polysaccharides fractions obtained from soybean, reported similar BS values for emulsions prepared under similar conditions …”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…No changes were observed in the %BS profiles or the %BS average values, so the emulsions were stable against creaming and coalescence. Porfiri et al ., working with insoluble polysaccharides fractions obtained from soybean, reported similar BS values for emulsions prepared under similar conditions …”
Section: Resultsmentioning
confidence: 68%
“…This reinforces the need to apply treatments that allow their use, such as the reduction of particle size by ultrasound treatment . Proteins are used as emulsifiers due to their ability to prevent droplet aggregation and coalescence, whereas only polysaccharides with sufficient hydrophobic characteristics, or those that are linked to proteins, enable the formation of stable emulsions by adsorbing them at the oil / water interface. Polysaccharides are therefore usually incorporated in emulsions to stabilize the droplets by increasing the viscosity of the continuous phase …”
Section: Introductionmentioning
confidence: 99%
“…At present, proteins, [40] polysaccharides, [41] and phospholipids [42] were widely reported as natural emulsifiers. At present, proteins, [40] polysaccharides, [41] and phospholipids [42] were widely reported as natural emulsifiers.…”
Section: Natural Emulsifiers Had Excellent Emulsifying Capacitymentioning
confidence: 99%
“…Dehydrated okara is composed of 55% whole fibre, 21% proteins, 13-14% fats and oils, 1.5% ash and 9-10% moisture [2]. Evidence from a recent study showed that okara insoluble polysaccharides (cellulose, hemicellulose and lignin) have emulsifying and rheological properties [3], and its proteins resemble soy protein isolate [4].…”
Section: Introductionmentioning
confidence: 99%